2015
DOI: 10.1111/ajd.12293
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis associated with cutaneous melanoma metastases

Abstract: We were able to validate the new AJCC melanoma staging system survival for patients with cutaneous metastatic disease. Patients presenting with regional cutaneous metastases have a much better prognosis than those with distant cutaneous metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the early stage, melanoma can be surgically removed, and the 5-year survival rate of melanoma patients is as high as 98% ( 5 ). Nevertheless, melanoma can easily metastasize to regional lymph nodes and result in poor prognosis, with a 5-year survival rate of only 16% ( 6 , 7 ). Various methods are used for the treatment of melanoma, including surgery, chemotherapy, radiation therapy, and immunotherapy ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the early stage, melanoma can be surgically removed, and the 5-year survival rate of melanoma patients is as high as 98% ( 5 ). Nevertheless, melanoma can easily metastasize to regional lymph nodes and result in poor prognosis, with a 5-year survival rate of only 16% ( 6 , 7 ). Various methods are used for the treatment of melanoma, including surgery, chemotherapy, radiation therapy, and immunotherapy ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, malignant melanoma easily metastasize to regional lymph nodes, and this is associated with a poor prognosis due to a lack of effective interventions. The overall survival of patients thus affected is only 6–9 months, and the 5-year survival rate is only 16% ( 8 , 9 ). Because malignant melanoma that has metastasized is not amenable to conventional radiotherapy and chemotherapy, it is particularly important to identify relvant molecular markers for early diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“… [26] Additionally, distant metastases and thickness of the primary CM were also found to be prominent negative predictors of the survival outcome. [27] After adjustment of multiple confounding factors through IPTW using the propensity score, such as gender, age, tumor histology, primary site and so on, our results showed that the patients undergoing surgical resection had a reduced risk of death compared with those without surgical resection, manifesting a superiority of surgical resection in survival outcome.…”
Section: Discussionmentioning
confidence: 74%